Harrowing the Gospels: A Cambodian (American) Rereading of Agriculture in Mark and Matthew - Coffman, Kristofer Dale Phan, (Biblical Interpretation Series ;, 2025)
Despite the growth in archaeology in the Galilee and sustained interest in the economic background of the Jesus movement, agriculture and agrarian life remain under-theorized in the study of the Gospels. Harrowing the Gospels: A Cambodian (American) Rereading of Agriculture in Mark and Matthew interrogates constructions of ethnography, economy, and ethnicity in previous Gospel research to both situate itself in and critique the gaps in the attention to these subjects. By reading from a Cambodian (American) perspective and through the tools of postcolonial and social-scientific analysis, this volume constructs a new working methodology fit to the problems of reading agriculture: "Postagrarian Analysis."